(untitled) (International Journal of Geoscience, Engineering and Technology, 2020)
The present paper has as its theme the geotechnical and structural analysis of anchored retaining wall into account the soil-structure interaction (SSI) and is based on a real case study. The objective of this study is to evaluate the influence that the consideration of the horizontal reaction coefficient (considering the Winkler hypothesis) on the wall/soil interface has on the requesting efforts, displacements mobilized in the wall and, consequently, on the structural design of the curtain. The analyzes showed that the variations of the horizontal reaction coefficient of the soil imply substantial variations of bending moments (around 30%), bending reinforcement armor (35% approximately) and displacements mobilized in the wall (950% approximately), results of redistribution of internal efforts, since the soil is no longer considered as an unshakable massif - a realistic design situation. Other aspects evaluated were: punching shear at the wall/anchor head interface and progressive collapse. The results obtained in the present work evidenced the importance of each of the analyzes and reinforced the need of the interface between the structural and geotechnical designers in the containment designs, treating the wall/anchor/soil assembly as the only one.